Crafting a competitive business development strategy for Java Aroma Essential: An MSME in the essential oil industry - Figueiredo, Jorge; Oliveira, Isabel; Cunha, Maria Nascimento (Seven Editora, 2024)
Java Aroma Essential (JAE), a Micro, Small, and Medium Enterprise (MSME) in an essential oil industry that urgently needs a robust development strategy to ensure business continuity. This study employs the Quantitative Strategic Planning Matrix (QSPM) method, gathering data through Focus Group Discussions (FGD) with both customers and company management. The Internal-External (IE) matrix places JAE in Quadrant I (Growth and Build), indicating a focus on intensive strategies such as market penetration, market development, and product development. The QSPM matrix further identifies the priority strategy as recruiting employees proficient in digital marketingThis research contributes significantly to the literature on MSME business strategy development, especially within the essential oil sector. The key recommendation is to enhance JAE’s market presence by hiring digital marketing experts. Few studies provide strategic insights for MSMEs in this industry, making this paper a valuable resource that offers a comprehensive development strategy and actionable steps for implementation. While the findings are tailored to MSMEs similar to JAE, future research should investigate broader applications across diverse MSME contexts. DOI:https://doi.org/10.56238/sevened2024.018-009